Effect of 5 VS 5 Small Sided Games (SSGs) Training on Passing Accuracy of U-16 Football Athletes - Gunawan; Abd Rahman (Journal of Physical and Outdoor Education, 2023)
The purpose of this study was to determine the effect of small sided games training on the passing accuracy of U-16 football athletes in Poso Regency. The method used is an experimental method with pre-test and post-test designs. Using the "treatment, pre-test and post-test" design, the population is U-16 athletes who are registered with the PSSI Poso Regency Association. The sampling method is purposive sampling technique, which is a sampling technique using certain criteria. This study used a pre-experimental design, namely a one-group pre-test-post-test design, in which there was no control group. The sample is 24 people. Data collection techniques using field tests. The type of test is a test of the accuracy of passing the ball towards the goal. Based on the paired sample t test where Pair 1, obtained a Sig value (2-Tailed 0.000 <0.05) it can be concluded that there is a difference in the average initial test of passing accuracy in U-16 soccer athletes before being given small sided games training is 4 .79 while the average value of the final test of passing accuracy is 7.33. This proves that there is an increase in the passing accuracy of U-16 football athletes in Poso Regency. Poso Regency U-16 football athlete.